Budidaya Sayuran Dengan Vertikultur Untuk Meningkatkan Ketahanan Pangan Rumah Tangga Masyarakat Komplek Perkotaan: id - Nasrah Natsir; Kartini Marzuki; Amir, Rudi; Latang; Febriansya (Program Studi Sarjana Terapan PTM FT UNM, 2025)
The growth of the population presents new challenges to food availability. One effort to enhance food adequacy, resilience, and self-sufficiency is the utilization of home garden spaces. However, in urban areas, limited land often becomes a barrier to maximizing yard use. Verticulture techniques offer a solution for vegetable cultivation in restricted spaces. This community service activity aims to introduce verticulture-based vegetable planting as a strategy to strengthen household food security. The participants consisted of residents from several housing complexes within the Somba Opu Subdistrict, Gowa Regency. The program was carried out through lectures and hands-on practice. The activity produced positive outcomes for the participants. Cognitively, their knowledge of verticulture-based vegetable cultivation increased significantly. Meanwhile, in terms of psychomotor skills, there was also an improvement in their ability to grow various types of vegetables using verticulture techniques.